The Scope of Serious Crime and Preventive Justice. Issue 3 (1st September 2016) - Sorell, Tom
Abstract : I first offer an account of serious crime that goes beyond victimizing crimes committed by individuals against other individuals. This approach extends the well-known framework offered by von Hirsch and Jareborg to include crimes undermining welfare-producing institutions. I then consider how the seriousness of crime justifies preventive measures, including the criminalization of acts preparatory to the commission of serious crime. I shall defend preventive measures, including highly intrusive ones, for the most serious crimes, such as terrorism in the form of mass killing, but I shall take issue with very expansive conceptions of serious crime that include what are intuitively much less serious offenses than terrorism or murder. In England and Wales, the Serious Crime Act (2007) lists relevant types of serious crime in its Schedule 1. This and other pieces of serious crime legislation in the UK are discussed critically.